Analisis Daya dan Biaya Penggunaan Low Sulfur Fuel Oil (LSFO) dengan High Sulfur Fuel Oil (HSFO) dilengkapi Scrubberpada Kapal Niaga - Bambang Wahyudi; Imam Fachruddin (Politeknik Ilmu Pelayaran Semarang, 2020)
Based on Marine Pollution (MARPOL) Convention Annex VI Regulation 14, commercial vessels are required to use low sulfur fuel (LSFO) with a sulfur content below 0.5% or continue to use heavy fuel (High Sulfur Fuel Oil - HSFO) with a sulfur content above 0.5% but you must install an exhaust gas cleaning system or scrubber. Indonesia is a member of the International Maritime Organization (IMO) so it must comply with these rules. This study aims to analyze the use of fuels with sulfur content below 0.5% or above 0.5% based on the power and costs incurred in order to comply with the Marpol Convention Annex VI Regulation 14. The data analysis techniques used in this study, for power, use Dulong formula, then the cost is reviewed from the comparison of the purchase of HSFO and LSFO along with the cost of purchasing and installing the scrubber. Based on the results of the study, it was concluded that the power produced by HSFO was greater than that of LSFO with a ratio of 1.15. Then, ship owners will get more profit if they invest in the purchase and installation of scrubbers on their ships than replacing the original HSFO fuel with LSFO.